Negative electrode material doped with metal oxide as well as preparation method and application of negative electrode material
By doping transition metal oxides in porous carbon and forming a core-shell structure, the problem of insufficient thermal stability and conductivity of the porous carbon matrix when combined with silicon is solved, and a higher performance silicon-carbon negative electrode material is achieved, extending the cycle life of the lithium-ion battery.
Patent Information
- Application Number
- CN202411726627.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
When combined with silicon, existing porous carbon matrix has problems such as insufficient thermal stability, insufficient conductivity, insufficient pore structure optimization, and agglomeration with silicon particles, which limits the improvement of the performance of silicon-carbon composite materials.
By doping specific transition metal oxides in porous carbon, such as tantalum oxide, tungsten oxide, molybdenum oxide, and niobium oxide, the overall conductivity and thermal stability of the porous carbon materials are improved, and the core-shell structure is formed through vapor deposition and cladding, the structural stability and cyclic performance of the electrode material are enhanced.
It achieves a more stable structure, higher conductivity and high temperature resistance, extends the cycle life of lithium-ion batteries, and improves the overall electrochemical performance of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion battery materials, and in particular to the preparation and application of a negative electrode material. Background Art
[0002] With the continuous growth of energy demand and the widespread application of portable electronic devices, lithium-ion batteries have become the main energy storage device due to their advantages such as high energy density, long cycle life and safety. However, traditional lithium-ion battery anode materials (such as graphite) have approached their theoretical limit in terms of energy density and are difficult to meet the growing energy demand. Therefore, finding and developing new anode materials has become an important direction of current lithium-ion battery research.
[0003] Silicon-based negative electrode materials have shown great potential in improving the energy density of lithium-ion batteries because of their ultra-high theoretical specific capacity (about 4200 mAh / g), which far exceeds that of graphite (372 mAh / g). However, silicon undergoes significant volume expansion and contraction during the charging and discharging process, up to more than 300%, resulting in structural damage to the electrode material, interface instability, and rapid decay of the cycle life. These problems have severely limited the promotion of silicon-based negative electrode materials in practical applications.
[0004] In order to overcome the volume expansion problem of silicon, the strategy of silicon-carbon composite materials is currently widely used, that is, by depositing silicon particles on a porous carbon matrix to form a silicon-carbon composite negative electrode material. As a matrix material, porous carbon has a high specific surface area, good conductivity and large porosity, which can buffer the volume expansion of silicon to a certain extent and provide an effective channel for the insertion and deinsertion of lithium ions. However, there are still some shortcomings in the current porous carbon in the process of combining with silicon, including insufficient thermal stability, insufficient conductivity, insufficient pore structure optimization and agglomeration with silicon particles, etc. These shortcomings limit the performance improvement of silicon-carbon composite materials. Summary of the invention
[0005] The present invention proposes a preparation method and application of porous carbon doped with specific transition metal oxides, the purpose of which is to solve the defects of existing porous carbon matrices, and to achieve the preparation and application of silicon-carbon negative electrode materials with more stable structure, high temperature resistance and better electrochemical performance. Among them, tantalum, tungsten, molybdenum and niobium oxides are preferably used, which do not conflict with the positive electrode materials of the battery, and the porous carbon is successfully doped with metal oxides, which can improve the overall conductivity of the porous carbon material and enhance the transmission efficiency of electrons; in addition, the high temperature resistance of the electrode material can be enhanced, so that it can better withstand the volume changes of silicon particles and be more adaptable to application scenarios in extreme environments, thereby extending the cycle life of the battery.
[0006] The present invention adopts the following technical solution: A metal oxide-doped negative electrode material comprises a porous carbon composite material containing the metal oxide.
[0007] Furthermore, the above-mentioned metal oxide-doped negative electrode material is a silicon-carbon negative electrode material. Specifically, the silicon-carbon negative electrode material includes the above-mentioned porous carbon composite material containing metal oxides and silicon-containing particles.
[0008] Furthermore, the above-mentioned metal oxide-doped negative electrode material is a core-shell structure, specifically, including the above-mentioned silicon-carbon negative electrode material and a coating layer on the surface of the silicon-carbon negative electrode material; preferably, the material of the coating layer includes at least one of carbon material, metal oxide and metal sulfide.
[0009] The present invention discloses a method for preparing the porous carbon composite material containing metal oxides, comprising the following steps: mixing a porous carbon raw material and a solution containing a metal salt, filtering, and heat treating to obtain a porous carbon composite material containing metal oxides. Specifically, the porous carbon raw material and the solution containing a metal salt are mixed, then filtered, and the filter cake is sequentially washed, dried, and heat treated to obtain a porous carbon composite material containing metal oxides.
[0010] The present invention discloses a method for preparing a silicon-carbon negative electrode material, comprising the following steps: (1) mixing a porous carbon raw material and a solution containing a metal salt, filtering, and heat treating to obtain a porous carbon composite material containing a metal oxide; (2) A porous carbon composite material containing metal oxides is vapor deposited with a silicon source gas to obtain a silicon-carbon negative electrode material.
[0011] The present invention discloses a method for preparing a core-shell structured silicon-carbon negative electrode material, comprising the following steps: (1) mixing a porous carbon raw material and a solution containing a metal salt, filtering, and heat treating to obtain a porous carbon composite material containing a metal oxide; (2) vapor-depositing a porous carbon composite material containing a metal oxide and a silicon source gas to obtain a silicon-carbon core; (3) A coating layer is formed on the surface of the silicon-carbon core to obtain a core-shell structured silicon-carbon negative electrode material.
[0012] Specifically, step (1) is: mixing a porous carbon raw material and a solution containing a metal salt, then filtering, and then washing, drying, and heat treating the filter cake in sequence to obtain a porous carbon composite material containing metal oxides.
[0013] Preferably, the heat treatment is carried out under inert gas at a temperature of 400-800° C. for a time of 3-10 h.
[0014] Specifically, step (2) is: in an inert atmosphere, vapor-depositing a porous carbon composite material containing metal oxides and a silicon source gas to obtain a silicon-carbon negative electrode material; preferably, the vapor deposition temperature is 400°C-900°C, and the time is 1-15h; the gas flow ratio of the silicon source gas to the inert gas is 1: (1-20).
[0015] Specifically, in step (3), forming a coating layer on the surface of the silicon-carbon core includes: forming the coating layer on the surface of the core by at least one of ball milling, mechanical stirring, mechanical fusion, atomic layer deposition, vapor deposition, magnetron sputtering, liquid phase reaction, sol-gel, solvent thermal, vacuum thermal deposition, plasma sputtering or melting. Preferably, the coating layer raw material gas is introduced into the silicon-carbon core, and a core-shell structure silicon-carbon negative electrode material is obtained after reaction; further preferably, the reaction temperature is 500°C-800°C, and the reaction time is 1h-12h; the coating layer raw material gas includes one or more of methane, ethane, propane, acetylene, propyne, butyne, propylene, and ethylene.
[0016] In the present invention, the metal salt includes a transition metal salt. Preferably, the transition metal salt includes one or more of tantalum salt, tungsten salt, molybdenum salt, and niobium salt. More preferably, the transition metal salt contains oxygen. As an example, the preferred metal salts of the present invention include ammonium tantalate (NH4[TaO(C2O4)2]), ammonium metatungstate ((NH4)6[H2W 12 O 40 ]·xH2O), ammonium molybdate ((NH4)2MoO4), ammonium niobate (NH4[NbO(C2O4)2]) or any one or more thereof.
[0017] In the present invention, the silicon source gas includes one or more of monosilane, disilane, trisilane and silicon tetrachloride.
[0018] In the present invention, the inert gas is one or more of nitrogen, helium, xenon, radon, neon and argon.
[0019] The invention discloses a negative electrode sheet, comprising the negative electrode material doped with metal oxide.
[0020] The invention discloses a lithium ion battery, comprising the negative electrode sheet.
[0021] The invention discloses an electrochemical device, comprising the lithium ion battery.
[0022] The invention discloses the application of the porous carbon composite material containing metal oxides, the negative electrode material doped with metal oxides or the negative electrode sheet in lithium ion batteries.
[0023] The negative electrode material provided by the present invention is a silicon-carbon negative electrode material with a doped metal oxide structure. A porous carbon raw material and a solution containing a metal salt are mixed, then filtered and heat-treated to obtain a porous carbon composite material containing metal oxides. Among them, tantalum oxide, tungsten oxide, molybdenum oxide, and niobium oxide, four transition metal oxides, are doped with porous carbon, which has good thermal stability and conductivity, and the doped negative electrode material will not conflict with the positive electrode material elements in the full battery.
[0024] In addition, the overall conductivity of porous carbon doped with tantalum, tungsten, molybdenum and niobium oxides is good, which helps to accelerate the transmission of electrons in the electrode and improve the reaction rate of silicon particles during the charge and discharge process; at the same time, the negative electrode material has high temperature resistance, which can enhance the thermal stability of the overall electrode material, thereby extending the cycle life of the battery. Especially in the application of lithium-ion batteries, these advantages are of great significance for the development of high-capacity and long-life electrode materials. DETAILED DESCRIPTION
[0025] In view of the shortcomings of current porous carbon, the present invention proposes a strategy of doping metal oxides in porous carbon. By introducing transition metal oxides into porous carbon, not only its thermal stability and conductivity can be improved, but also the overall structural stability and cycle performance of the electrode material can be improved. The method of the present invention is expected to further enhance the electrochemical performance of silicon-carbon composite materials and provide an effective way for the development of high energy density lithium-ion batteries.
[0026] The present invention immerses the porous carbon raw material into a solution containing a metal salt by an impregnation method, stirs and mixes evenly to obtain a mixed solution; after the uniform mixing is completed, suction filtration, washing, drying and heat treatment are performed in sequence to obtain a porous carbon composite material containing metal oxides. Then, under an inert gas, the porous carbon composite material containing metal oxides is vapor deposited with a silicon source gas to obtain a porous carbon composite material including porous carbon, metal oxides and nano-silicon particles, which is a silicon-carbon negative electrode material or a silicon-carbon core. Further, a coating layer is formed on the surface of the silicon-carbon core to obtain a core-shell structured silicon-carbon negative electrode material.
[0027] In the present invention, the metal salt is a water-soluble or alcohol-soluble metal salt, preferably ammonium tantalate (NH4[TaO(C2O4)2]), ammonium metatungstate ((NH4)6[H2W 12 O 40 ]·xH2O), ammonium molybdate ((NH4)2MoO4), ammonium niobate (NH4[NbO(C2O4)2]).
[0028] In the above technical solution, in the mixed solution, the concentration of the metal salt is 0.1M-1M, the concentration of the porous carbon raw material is 0.1~20wt%; the solvent is water or a small molecule alcohol, such as ethanol.
[0029] In the above technical solution, stirring and mixing uniformly is a conventional technique, for example, the stirring temperature is 20-80° C. and the time is 6-18 hours.
[0030] In the above technical solution, the heat treatment is carried out under inert gas at a temperature of 400-800°C for 5-8h.
[0031] In the above technical solution, the temperature of vapor deposition is 400°C-800°C, such as 500°C, 600°C, 700°C or any temperature within the range; the time of vapor deposition is 4-12h; and the gas flow ratio of silicon source gas and inert gas is 1: (5-10).
[0032] In the above technical solution, the coating layer is preferably a carbon coating layer. Carbon coating itself is a conventional technology, and gas phase carbon coating, liquid phase or solid phase coating can be used, wherein the gas source of the gas phase carbon coating includes hydrocarbons, such as the gas source used for gas phase coating is one or more of methane, ethane, propane, acetylene, propyne, butyne, propylene, and ethylene. Preferably, the temperature of the gas phase carbon coating is 300-1000°C, such as 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or any temperature in the range; preferably, the carbon coating time is 1-10h, such as 2h, 3h, 4h, 5h, 7h, 9h or any time in the range; in the present invention, the gas phase carbon coating insulation process can be a one-stage insulation or a segmented insulation.
[0033] The present invention also provides a negative electrode sheet, comprising the above-mentioned silicon-carbon negative electrode material with a doped metal oxide structure. The present invention does not specifically limit the preparation method of the negative electrode sheet, and methods known to those skilled in the art are sufficient. For example, the negative electrode active material, the conductive material, the binding material and water are mixed, and the solid content is controlled to be 60-80% to obtain a negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector, dried, and pressed to obtain a negative electrode sheet. The negative electrode active material is selected from the above-mentioned silicon-carbon negative electrode material with a doped metal oxide structure, or a mixed material of the above-mentioned silicon-carbon negative electrode material with a doped metal oxide structure and a graphite negative electrode material; wherein the graphite negative electrode material is one or more of artificial graphite, natural graphite, and modified graphite; when the negative electrode active material is a mixed material of the above-mentioned silicon-carbon negative electrode material with a doped metal oxide structure and a graphite negative electrode material, the silicon-carbon negative electrode material with a doped metal oxide structure accounts for 30-70% of the mass of the mixed material, preferably 40-60%.
[0034] The bonding material is selected from one or more of acrylonitrile, vinylidene fluoride, vinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, methacryloyl, acrylic acid, lithium acrylate, acrylamide, amide, imide, acrylate, styrene-butadiene rubber, sodium alginate, chitosan, and ethylene glycol; the conductive material is one or more of conductive carbon black, acetylene black, graphite, graphene, carbon micro-nanowires, and carbon micro-nanotubes; the negative electrode current collector may include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, foam nickel, foam copper, or a composite current collector.
[0035] The negative electrode active material, the conductive material, and the binding material are mixed in a mass ratio of (7-9):(0.5-1.5):(0.5-1.5). The mass percentage of the negative electrode active material is preferably 75-85%, more preferably 78-82%, for example 78%, 79%, 80%, 81%, 82% or any percentage within the range.
[0036] The present invention also provides a lithium ion battery, comprising the above-mentioned negative electrode sheet. The specific preparation method and composition of the lithium ion battery are not particularly limited, and methods known to those skilled in the art can be used, which may include but are not limited to: lithium metal secondary battery, lithium ion secondary battery, lithium polymer secondary battery or lithium ion polymer secondary battery, etc.
[0037] As an example, a negative electrode sheet, a separator, and a positive electrode sheet are wound to obtain a battery cell, and the battery cell is placed in a battery case, dried, injected with electrolyte, packaged, formed, and divided into different capacities to obtain a lithium-ion battery.
[0038] Now, various exemplary embodiments of the present invention are described in detail. The detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, features and embodiments of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by a person skilled in the art in the field of the present invention. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe methods and / or materials related to the documents. The raw materials used in the present invention are existing products that meet the conventional requirements of lithium-ion battery silicon-carbon negative electrode materials. Specific preparation operations (such as specific operations such as dispersion, mixing, drying, heat treatment, etc.) and performance tests are all conventional techniques. The porous carbon raw material is a conventional product in the art, including resin materials or biomass materials, wherein the resin material includes one or more mixtures of phenolic resin, furfural resin, polyurethane resin, urea-formaldehyde resin, polyacrylonitrile resin, alcohol-soluble resin, acrylic resin, and polyimide resin; the biomass material is one or more mixtures of sawdust, coconut shell, and bamboo powder.
[0039] Unless otherwise specified, the silane used in the experiment was monosilane, and the porous carbon raw material was phenolic resin (model: PF-1556).
[0040] Example 1 The preparation of a porous carbon composite material containing metal oxides is as follows: Dissolve ammonium tantalate (NH4[TaO(C2O4)2]) in deionized water to prepare a 0.5M metal salt solution. Add the porous carbon raw material to 400mL of the 0.5M metal salt solution by impregnation, with the mass fraction of the porous carbon raw material being 10wt%; stir at room temperature for 10h, and allow the metal salt solution to penetrate into the porous carbon material. After the impregnation is completed, the mixture is vacuum filtered and the filter cake is filtered with a mixture of anhydrous ethanol and deionized water (V 去离子水 :V 无水乙醇 =1:1) was washed repeatedly three times, and then dried in an oven at 80°C for 12 hours; the dried material was calcined in a tube furnace at 600°C for 8 hours under a nitrogen atmosphere to obtain a porous carbon material doped with tantalum oxide; Then, 1.5 kg of porous carbon material doped with tantalum oxide was placed in a deposition furnace, nitrogen was introduced into the deposition furnace at a gas flow rate of 15 L / min for protection, and the deposition furnace was heated from room temperature to 600° C. at a heating rate of 2° C. / min, and kept warm for 35 minutes, and then a mixed gas of monosilane and nitrogen was introduced at a ratio of 10 L / min:50 L / min, and the temperature was kept warm for 5.5 hours, so that the porous carbon material and monosilane were vapor-deposited to obtain a porous silicon-carbon composite material including porous carbon, metal oxides and nano-silicon particles, which was a silicon-carbon core; Finally, stop introducing monosilane and instead introduce only nitrogen for 30 minutes to remove residual gas; then continue to introduce a mixed gas of acetylene and nitrogen with a mixed flow rate ratio of acetylene and nitrogen set to 6L / min and 6L / min, and continue to maintain this temperature and mixed gas environment for 3 hours, and naturally cool to room temperature to form a negative electrode material with a carbon layer shell and an inner core, which serves as a silicon-carbon negative electrode material.
[0041] Afterwards, the prepared negative electrode material is used to prepare a pole piece of a lithium-ion battery, and the pole piece is used to assemble a button-type half-cell for testing, which is a conventional technology and is briefly described as follows: First, the negative electrode material, conductive agent Super P and binder lithium polyacrylic acid were added to a mortar in a mass ratio of 8:1:1 for grinding, then added to deionized water, and beaten in a beater to form a slurry, which was then coated on the copper foil current collector. After that, it was dried in a vacuum oven at 80°C for 12 hours, and then the dried pole piece was cut into a disc with a diameter of 14 mm as the pole piece of the button half-cell; Secondly, the above-mentioned electrode pieces were assembled into button-type half-cells in an argon-filled glove box. The aqueous electrolyte of the button-type half-cell is 1 mol / L lithium hexafluorophosphate LiPF6, and the solvent of the electrolyte is ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC), wherein the volume ratio of EC, DMC and DEC is 1:1:1, and it also contains 5% fluoroethylene carbonate (FEC) as an additive; the counter electrode is a lithium sheet.
[0042] Finally, according to conventional methods, the electrochemical performance was evaluated by testing on a blue battery test system under the following test conditions: voltage window 0.01V-2V.
[0043] Comparative Example 1 Referring to Example 1, the metal oxide doping was omitted, that is, the porous carbon raw material was added to 400 mL of solution, the mass fraction of the porous carbon raw material was 10 wt%, and vacuum filtration was performed after conventional stirring. The filter cake was dried in an oven at 80°C for 12 h; the dried material was calcined at 600°C in a tubular furnace under a nitrogen atmosphere for 8 h to obtain a porous carbon material; 1.5 kg of the porous carbon material was placed in a deposition furnace, and monosilane was vapor deposited and carbon coated according to Example 1 to obtain a porous silicon-carbon core-shell composite material including porous carbon and nano-silicon particles as a negative electrode material.
[0044] Comparative Example 2 Referring to Example 1, the type of metal oxide was changed, that is, a certain amount of ferric chloride (FeCl3) was dissolved in deionized water to prepare a metal salt solution with a concentration of 0.5M. The porous carbon raw material was added to 400mL of a 0.5M metal salt solution by an impregnation method, and the mass fraction of the porous carbon raw material was 10wt%; the porous carbon material was impregnated for 10h at room temperature with conventional stirring, and the metal salt solution was fully immersed in the porous carbon material.
[0045] After the impregnation is completed, the mixture is vacuum filtered and the filter cake is filtered with a mixture of anhydrous ethanol and deionized water (V 去离子水 :V 无水乙醇 =1:1) was washed repeatedly three times and then dried in an oven at 80°C for 12 h; the dried material was calcined at 600°C in a tubular furnace under a nitrogen atmosphere for 8 h to obtain a porous carbon material doped with iron oxide.
[0046] Afterwards, the deposition of silicon particles, carbon coating, assembly of button half cells and testing were the same as in Example 1.
[0047] Comparative Example 3 Referring to Example 1, the type of metal oxide was changed, and the ammonium tantalate was replaced with an equal amount of nickel nitrate (Ni(NO3)2), and the rest was the same, to obtain a porous carbon material doped with nickel oxide. Thereafter, the deposition of silicon particles, carbon coating, assembly of button half-cells, and testing were the same as in Example 1.
[0048] Comparative Example 4 Referring to Example 1, the type of metal oxide was changed, and ammonium tantalate was replaced with an equal amount of manganese nitrate (Mn(NO3)2), and the rest was the same to obtain a porous carbon material doped with manganese oxide. Thereafter, the deposition of silicon particles, carbon coating, assembly of button half-cells, and testing were the same as in Example 1.
[0049] Comparative Example 5 Porous Carbon Impregnation Referring to Example 1, the porous carbon raw material is replaced with a resin-based porous carbon prepared by a conventional method (the carbon precursor phenolic resin (model: PF-1833) is physically activated by water vapor), and the rest is the same to obtain a porous silicon-carbon core-shell composite material including porous carbon, metal oxides and nano-silicon particles as a negative electrode material. Example 2
[0050] Different from Example 1, in this embodiment, the addition amount of ammonium tantalate (NH4[TaO(C2O4)2]) is adjusted to: its concentration in water is 0.1M; the rest is the same. Example 3
[0051] Different from Example 1, in this example, the amount of ammonium tantalate (NH4[TaO(C2O4)2]) added is adjusted to a concentration of 1 M in water; the rest remain the same. Example 4
[0052] Different from Example 1, in this example, the amount of porous carbon raw material is adjusted to a concentration of 0.1 wt % in the metal salt solution; the rest are the same. Example 5
[0053] Different from Example 1, in this example, the amount of porous carbon raw material is adjusted to a concentration of 20 wt % in the metal salt solution; the rest are the same. Example 6
[0054] Different from Example 1, in this example, ammonium tantalate (NH4[TaO(C2O4)2]) is replaced by an equal mass of ammonium metatungstate ((NH4)6[H2W 12 O 40 ]·xH2O); the rest are the same. Example 7
[0055] Different from Example 1, in this example, ammonium tantalate (NH4[TaO(C2O4)2]) is replaced by an equal mass of ammonium molybdate ((NH4)2MoO4); the rest is the same. Example 8
[0056] Different from Example 1, in this embodiment, ammonium tantalate (NH4[TaO(C2O4)2]) is replaced by an equal mass of ammonium niobate (NH4[NbO(C2O4)2]); the rest is the same. Example 9
[0057] Different from Example 1, in this example, the stirring temperature is set to 40° C. and the stirring time is 18 h; the rest is the same. Example 10
[0058] Different from Example 1, in this example, the stirring temperature is set to 80° C. and the stirring time is 6 h; the rest is the same. Embodiment 11
[0059] Different from Example 1, in this example, the heat treatment temperature is 400° C. and the time is 12 h; the rest are the same. Example 12
[0060] Different from Example 1, in this embodiment, the heat treatment temperature is 800° C. and the time is 4 hours; the rest is the same.
[0061] Table 1 Rate performance test data of button-type half-cells prepared in Examples 1-12 and Comparative Examples 1-5
[0062] As can be seen from Table 1, compared with Comparative Examples 1-5, the button-type half-cell of the embodiment of the present invention shows significant excellence in cycle stability. This is because the negative electrode material in the present invention enhances the conductivity and structural stability of the material by doping a certain proportion of metal oxides, which helps to maintain the integrity of the electrode during the charge and discharge process. The doped metal oxide improves the pore structure of the carbon-based material, increases the specific surface area and pore volume, and thus accelerates the migration rate and embedding efficiency of lithium ions. The pore structure in the porous carbon effectively buffers the volume change of silicon particles during the charge and discharge process, so that the electrode material maintains good cycle performance under high rate conditions, reduces the internal stress of the battery, and prolongs the battery life. Ultimately, the material of the present invention can not only significantly improve the rate performance of the battery, but also effectively slow down the capacity decay, ensuring the stability of the battery during long-term cyclic use.
[0063] Table 2 Comparative data of the capacity retention rate of button-type half-cells prepared in Examples 1-12 and Comparative Examples 1-5
[0064] Table 2 is a comparison of the capacity retention rates of button-type half-cells prepared in Examples 1-12 and Comparative Examples 1-5 at a current density of 0.1C, a temperature of 80°C, and 100 cycles. As can be seen from Table 2, compared with Comparative Examples 1-5, the capacity retention rates of the button-type half-cells in the embodiments of the present invention at a current density of 0.1C, a temperature of 80°C, and 100 cycles are all maintained at more than 80%. This is because the negative electrode material of the present invention is impregnated with metal compounds starting from porous carbon raw materials, and the obtained negative electrode material is doped with thermally stable metal oxides, which significantly improves the high temperature resistance of the composite material. The doped metal oxide not only enhances the structural stability of the material, but also effectively improves the durability of the electrode at high temperatures, and reduces the degradation of the material caused by stress and volume expansion in a high temperature environment. Such improvements help to maintain a stable lithium ion transmission channel under high temperature conditions, thereby reducing the loss of capacity during charging and discharging, and improving the cycle performance and safety of the battery. Finally, the material of the present invention exhibits excellent cycle retention and long-term high temperature stability, so that the battery can still maintain excellent electrochemical properties under harsh environments.
Claims
1. A negative electrode material doped with a metal oxide, characterized in that: Includes porous carbon composite materials containing metal oxides.
2. The metal oxide-doped negative electrode material according to claim 1, characterized in that: The metal oxide-doped negative electrode material is a silicon-carbon negative electrode material.
3. The metal oxide-doped negative electrode material according to claim 2, characterized in that: The metal oxide-doped negative electrode material is a core-shell structure.
4. The method for preparing the porous carbon composite material containing metal oxide for the negative electrode material doped with metal oxide according to claim 1, characterized in that: The method comprises the following steps: mixing a porous carbon raw material and a solution containing a metal salt, filtering, and heat treating to obtain a porous carbon composite material containing metal oxides.
5. The method for preparing the negative electrode material doped with metal oxide according to claim 2, characterized in that: The following steps are involved: (1) mixing a porous carbon raw material and a solution containing a metal salt, filtering, and heat treating to obtain a porous carbon composite material containing a metal oxide; (2) A porous carbon composite material containing metal oxides is vapor deposited with a silicon source gas to obtain a silicon-carbon negative electrode material.
6. The method for preparing the negative electrode material doped with metal oxide according to claim 3, characterized in that: The following steps are involved: (1) mixing a porous carbon raw material and a solution containing a metal salt, filtering, and heat treating to obtain a porous carbon composite material containing a metal oxide; (2) vapor-depositing a porous carbon composite material containing a metal oxide and a silicon source gas to obtain a silicon-carbon core; (3) A coating layer is formed on the surface of the silicon-carbon core to obtain a core-shell structured silicon-carbon negative electrode material.
7. The preparation method according to claim 4, 5 or 6, characterized in that: The heat treatment is carried out under an inert gas at a temperature of 400-800° C. for a time of 3-10 hours; the metal salt includes a transition metal salt.
8. The preparation method according to claim 7, characterized in that: The transition metal salt includes one or more of tantalum salt, tungsten salt, molybdenum salt and niobium salt.
9. A negative electrode sheet or a lithium ion battery comprising the negative electrode material doped with metal oxide according to claim 1, 2 or 3.
10. Use of the metal oxide-doped negative electrode material of claim 1, 2 or 3 or the negative electrode sheet of claim 9 in a lithium-ion battery.
Citation Information
Cited By
Silicon-carbon negative electrode material, preparation method thereof and secondary battery
CN120690848A
Silicon-carbon negative electrode material and preparation method thereof
CN122224820A